2016
DOI: 10.1007/s10886-016-0701-3
|View full text |Cite
|
Sign up to set email alerts
|

Tarsi of Male Heliothine Moths Contain Aldehydes and Butyrate Esters as Potential Pheromone Components

Abstract: The Noctuidae are one of the most speciose moth families and include the genera Helicoverpa and Heliothis. Females use (Z)-11-hexadecenal as the major component of their sex pheromones except for Helicoverpa assulta and Helicoverpa gelotopoeon, both of which utilize (Z)-9-hexadecenal. The minor compounds found in heliothine sex pheromone glands vary with species, but hexadecanal has been found in the pheromone gland of almost all heliothine females so far investigated. In this study, we found a large amount (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
2
16
1
Order By: Relevance
“…One of the minor components, 16:Ald is found in pheromone glands at trace levels but is not required for male attraction, therefore is not considered a sex pheromone in H. zea (Hillier and Baker, 2016). Relative to our study, 16:Ald was found in legs of heliothine moths: a large amount (0.5-1.5 μg) in male tarsi and a lower amount (0.05-0.5 μg) in female tarsi, (Choi et al, 2016). However, the biological role of 16:Ald in the legs of heliothines is still unclear.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…One of the minor components, 16:Ald is found in pheromone glands at trace levels but is not required for male attraction, therefore is not considered a sex pheromone in H. zea (Hillier and Baker, 2016). Relative to our study, 16:Ald was found in legs of heliothine moths: a large amount (0.5-1.5 μg) in male tarsi and a lower amount (0.05-0.5 μg) in female tarsi, (Choi et al, 2016). However, the biological role of 16:Ald in the legs of heliothines is still unclear.…”
Section: Discussioncontrasting
confidence: 93%
“…Two PBAN receptor isoforms were more abundant in PGs than tarsi. Removing the source of PBAN by decapitation did not reduce the 16:Ald amounts in tarsi indicating the production of 16:Ald in tarsi is not under PBAN control (Choi et al, 2016). In addition, we found transcripts encoding for four other GPCRs: DHR, ETHR, SPR, and OctoR.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In conclusion, our results demonstrate that females of H. virescens possess the pheromone detection elements (pheromone receptors, PBPs and SNMP1), which would enable them to “autodetect” a sex pheromone component but also to sense other pheromones. Compounds released from conspecifics, such as male hairpencil compounds (Hillier & Vickers, ) or the newly discovered components released from male tarsi (Choi et al ., ) are considered as candidates. Although, similar molecular elements for pheromone detection were found in the two sexes; significant differences between sexes emerged, including the spatial segregation of SNMP1 cells (cluster vs. solitary) and the coexpression of HR11 and SNMP1 in females but not in males.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that our findings could be attributed to this male pheromone compound and not to any odor that changes the female’s odor, we also perfumed virgin females with 100 ng hexadecanal (16:Ald). This compound is present in the female sex pheromone gland3940 and on the male’s tarsi41 and perceived by both males and females42, but it has not been shown to affect male attraction43.…”
Section: Methodsmentioning
confidence: 99%